2020
DOI: 10.1097/pr9.0000000000000851
|View full text |Cite
|
Sign up to set email alerts
|

Patient-centered prescription opioid tapering in community outpatients with chronic pain: 2- to 3-year follow-up in a subset of patients

Abstract: Study findings reveal continued opioid reduction and enduring pain stability for a substantial fraction of patients, 2 to 3 years after a patient-centered voluntary opioid tapering program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…A follow-up study on a subset of patients found that their dose reductions and pain stability were maintained 2 to 3 years later. 36 These findings suggest that this individualized consensual approach promotes successful opioid dose reduction.…”
mentioning
confidence: 94%
“…A follow-up study on a subset of patients found that their dose reductions and pain stability were maintained 2 to 3 years later. 36 These findings suggest that this individualized consensual approach promotes successful opioid dose reduction.…”
mentioning
confidence: 94%
“…All except one (Chang et al, 2014 ) were offered in specialist pain service settings. Less structured information and education was provided in a pain service setting where the goal was to sequentially stabilise opioid dose then taper (Kurita et al, 2018 ) and patient‐centred ‘Prescription Opioid Tapering’ appointments, partnering with the prescribing physician (Darnall et al, 2018 ; Ziadni et al, 2020 ). A number of primary care settings also offered a more informal approach with physician‐ patient discussion of ethical principles and evidence‐based practice (Goodman et al, 2018 ), communication about opioid management for chronic pain (Matthias et al, 2017 ) and holistic care using self‐management principles through the South Gloucestershire pain review service (Scott et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported statistically significant opioid reduction but noted a similar reduction was evident in the comparator group (Goodman et al, 2018 ; Sullivan et al, 2017 ) and a small number of studies showed statistically significant opioid reduction during the intervention period that was not maintained to the final study endpoint (Garland et al, 2014 ; Zheng et al, 2008 , 2019 ). Participants at specialist pain services started with higher opioid doses with the average starting dose reported as 193mg morphine equivalent dose (MED) (Gurino et al, 2018 ; Kurita et al, 2018 ; Naylor et al, 2010 ; Sullivan et al, 2017 ; Zheng et al, 2008 , 2019 ; Ziadni et al, 2020 ) in contrast to the average dose of 85mg MED reported in studies from primary care clinics (Doolin, 2017 ; Goodman et al, 2018 ; Mehl‐Madrona et al, 2016 ; Scott et al, 2020 ). Setting and delivery of interventions for opioid reduction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an effort to reduce the harms associated with long-term opioid use, the Department of Defense (DoD)/Veterans Affair (VA) and the Centers for Disease Control (CDC) have published guidelines that recommend limiting prescriptions of opioids for the management of chronic pain to no more than 90 morphine milligram equivalents (MME) a day ( 1 3 ). While there is burgeoning evidence regarding the potential benefits of opioid tapering ( 4 7 ), debate persists about tapering methods, challenges, and potential harms, including increased risk of drug overdoses and mental health crises ( 8 10 ). In addition, there is limited empirical evidence to support best practices for successful opioid tapering in patients with chronic pain ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%